Supplementary effects of low-frequency transcutaneous electrical nerve stimulation on individuals with obesity combined with metabolic syndromes: study protocol for a randomised controlled trial - Xi Chen; Xiang Li; Lei Yang; Wei Zhang; An Yu; Liuyan Wang; Mei Xie; Lifen Wen; Bijuan Liang; Yazhou Zhang (BMJ Open)
Introduction Obesity combined with metabolic syndrome is a major global public health problem. This trial aims to investigate the therapeutic effects of low-frequency transcutaneous electrical nerve stimulation (Lo-TENS) in individuals with obesity and coexisting metabolic syndrome. The study will also delve into the underlying mechanisms through which Lo-TENS may mitigate the symptoms of metabolic syndrome, providing insights into its potential as a novel treatment approach.Methods and analysis This randomised controlled trial will enrol 63 individuals with obesity and metabolic syndrome, and randomly assign them to one of the three groups: (1) peripheral stimulation group, (2) central stimulation group and (3) sham stimulation group. Each participant will receive a 30 min daily session of their assigned stimulation, conducted 5 days a week for a duration of 12 weeks. The primary outcomes of interest are body mass index and fasting blood glucose, with secondary outcomes encompassing blood pressure, triglyceride levels and various metabolic biomarkers. Comprehensive assessments will be performed at baseline, immediately post intervention, and followed by a 12-week follow-up evaluation to monitor long-term effects and sustainability of potential benefits.Ethics and dissemination The trial has been granted ethical approval by the ethics committee of the Second People’s Hospital of Kunming (approval number: 202305001). The study’s findings will be disseminated through peer-reviewed journal publications and international conference presentations.Trial registration number Chinese Clinical Trial Registry Platform: www.chictr.org.cn (No. ChiCTR2400089104).